Dampak Media Sosial terhadap Pola Perilaku Berbahasa Anak Pra-Remaja : Sebuah Tinjauan Psikolinguistik - Fenesiana Claudina Eunike Tabun; Maria Elisabeth Bria; Ramires Mario Lurdes Bria; Selestina Luruk Seran; Emeliana Tai (Institut Nalanda, 2025)
More than 191 million people currently use social media, more over now we have entered the digital generation. The era of technology meets daily needs. It is imposible that among the 139 are children in pre-adolescence. In the pre-adolescent period, children experience many change, both physical and psychological changes in their growth. Which can influence the child’s language behavior. Therefore, this research aims to see how far the influence of social media on teenagers language behavior. The method used in this research is descriptive qualitative with data collection methods using listening and skill methods. As well as data collection techniques using recording and note-taking techniques. The data source in this research is field note data as well as interviews with the child. The result of qualitative research are needed by researchers this is in-depth related information the influence of social media on pre-teen children. Such as a lack of communication with the surrounding environment or use language that is not standard or appropriate.